Medios de comunicación escrita y la práctica de la lectura en los jóvenes de la Unidad Educativa San Camilo, Ciudad de Quevedo, año 2019 - Sánchez Estupiñán, Gabriela Alejandra (2020)
With the research process carried out during this degree project, several important aspects have been determined in the context of written media and reading in young people. Journalism and the media have not been left out, in fact, they have undergone constant transformation and adaptation, due to the progress of social networks. Precisely, this work is intended to analyze and study the influence of written media and detect both strengths and weaknesses when influencing the habit of reading and writing in the youth of the San Camilo Educational Unit, of the canton Quevedo. In the first chapter, the topic to be investigated based on their respective contexts will be announced, raising appropriate objectives to solve the problem by defining their variables for the development of research. Chapter two will be framed in their respective theoretical and bibliographic support backed by the most representative authors attached to the problem that is being investigated to support the hypotheses of the case, in addition chapter three will detail the results of the research represented through tables and graphs Statisticians for correct interpretation and analysis. Consequently, chapter four will establish the alternative proposal to solve the problem raised during the development of the investigation, with the purpose of applying a guide with instructional workshops, in addition to the appropriate conclusions and recommendations with the aim of solving the problems found in the media. of communication for the benefit of the Educational Unit “San Camilo”